PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS IV SD NEGERI 64 LUBUKLINGGAU - Diyah Septiana; Asep Sukenda Egok; Armi Yuneti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the completeness of the social studies learning outcomes of grade IV students of SD Negeri 64 Lubuklinggau after using the Contextual Teaching and Learning (CTL) learning model. The research method used is a quantitative method with a research design in the form of One Group Pretest-posttest design. The sampling technique used is random sampling. Data collection was carried out using a test technique consisting of 10 essay questions. Data analysis techniques consist of prerequisite analysis techniques and hypothesis testing. The prerequisite analysis testing technique uses a normality test while the hypothesis used is the t-test. The results of the study showed an average pre-test learning outcome (46.11) and post-test (78.33). Based on the results of the t-test analysis, the average (x) value of the overall final test results based on the calculation was 78.33. Chitable is 9.488 and χ²count 1.5108. Because χ²count 1.5108 < χ²table 9.488 then the data can be concluded to be normally distributed, the magnitude of tcount = 3.22 and ttable = 1.739 with a significance level of 5% and dk = n-1 because tcount = 3.22 > ttable = 1.739 then the hypothesis is accepted meaning the average value of the results of social studies learning of grade IV students of SD Negeri 64 Lubuklinggau after the implementation of the Contextual Teaching and Learning learning model is significantly complete.